Design and Performance Test of Relative Humidity and Temperature Controlling Devices Using the Micro controller AT89C51 for Drying - S., Sumardi H.; Argo, Bambang Dwi; Umniyati, Dian (Jurnal Teknologi Pertanian, 2005)
The objectives of this research were to design and to produce relative humidity and temperature controlling devices using the Micro controller AT89C51 hardware and to control the heater performance of a dryer. The works was carried out in three stages: designing, constructing and performance testing of the devices. The associated apparatus includes the SHT 75 sensor, a keypad, an LCD, and a driver relay. The â€œAssemblerâ€ language was used to develop a computer software. The output of measurements of the product temperatures and relative humidities of the air were used to control the heater and blower operation during drying.Â  The readings of the developed devices were compared with the ones using the corresponding conventional apparatus. The results showed that the devices works well for measurement of a set values of RH and temperature. Compared with the conventional method, the difference in readings were in the order of 0.07oC to 0.53oC (temperature) and 0.16 to 0.98% for RH in the range of RH between 75 â€“ 79%. Â  Key words: temperature and RH control, drying, Micro controller AT89C51, SHT75 sensor